PERKULIAHAN DARING PADA MATA KULIAH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI STAI DARUL ULUM KANDANGAN KALIMANTAN SELATAN - Hairidah (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2020)
Based on the government`s appeal about prevention of the covid-19 outbreak to carry out learning activities from home, even learning process in a college. The learning process was carried out from home by utilizing internet technology. This study aims to review Online Lectures in Islamic Religious Education Subjects including Jurisprudence Learning, Islamic Cultural History, Akidah Akhlak, Alquran Hadith, at STAI Darul Ulum Kandangan, South Kalimantan. Results of this study found most lecturers use WhatApp and Youtube as media of lecturing, an absence system different, some lecturers by giving 15 minutes to attend. The monitoring carried out mostly viewed students acitivity of appearing in the WhatApp group, while the evaluation was partially using process evaluation which meant that the lecturer always monitored student activeness in online lectures. In terms of supporting and inhibiting factors, it can be concluded that learning lecturers do not feel hampered by internet quota and internet networks, it's just that some students complain that they have to have a lot of quota especially this learning requires them to upload teaching practice videos and it requires adequate quota and internet network. In terms of lecturers, only some felt that they were hampered by the time available.